The Detection of Prostate Cancer with Magnetic Resonance Imaging-Targeted Prostate Biopsies is Superior with the Transperineal vs the Transrectal Approach. A European Association of Urology-Young Academic Urologists Prostate Cancer Working Group Multi-Institutional Study. Issue 4 (9th October 2022) - Zattoni, Fabio; Marra, Giancarlo; Kasivisvanathan, Veeru; Grummet, Jeremy; Nandurkar, Rohan; Ploussard, Guillaume; Olivier, Jonathan; Chiu, Peter K.; Valerio, Massimo; Gontero, Paolo; Guo, Hongqian; Zhuang, Junlong; et al.
Abstract : Purpose: Our aim was to evaluate whether transperineal (TP) MRI-targeted prostate biopsy (TBx) may improve the detection of clinically significant prostate cancer (csPCa), defined as International Society of Urological Pathology ≥2, in comparison to transrectal (TR) TBx. Materials and Methods: A multicenter retrospective cohort study comprising patients who underwent MRI-guided prostate biopsy was conducted. To address possible benefits of TP-TBx in the detection of prostate cancer (PCa) and csPCa, a cohort of patients undergoing TP-TBx were compared to patients undergoing TR-TBx. Multivariable logistic regression analyses were performed to assess predictors of PCa and csPCa detection. Results: Overall, 1, 936 and 3, 305 patients who underwent TR-TBx vs TP-TBx at 10 referral centers were enrolled. The rate of PCa and csPCa diagnosed was higher for TP-TBx vs TR-TBx (64.0% vs 50%, p <0.01 and 49% vs 35%, p <0.01). At multivariable analysis adjusted for age, biopsy naïve/repeated biopsy, cT stage, Prostate Imaging–Reporting and Data System®, prostate volume, PSA, and number of biopsy cores targeted, TP-TBx was an independent predictor of PCa (odds ratio [OR] 1.37, 95% CI 1.08–1.72) and csPCa (1.19, 95% CI 1.12–1.50). When considering the approach according to the site of the index lesion, TP-TBx had a significantly higher likelihood than TR-TBx to detect csPCa in the apex (OR 4.81, 95% CI 1.03–6.27), transition/central zone (OR 2.67, 95% CI 1.42–5.00), and anterior zone (OR 5.62, 95% CI 1.74–8.13). Conclusions: The use of TP-TBx allows a better cancer grade definition and PCa risk assessment. This has important implication in the decision-making process and in patient counseling for further therapies.